Prendre en compte la parole des enfants de six à onze ans et révéler leur statut d’informateurs particuliers : l’apport des méthodes visuelles - Sophie Levrard (Recherches en Éducation)
This article, based on doctoral research in education, shows how a visual survey method can collect and give a privileged status to children’s speech. The photographic journey, the interviews of ecitation and the video form a methodological triangle that allows to obtain data on the ways of inhabiting the school as close as possible to the childlike representations. Childhood photographies and speeches reveal in children an ability to territorialize according to what is available to them and according to the permissions granted by adults.